Deep Sequencing Transcriptome Analysis of Murine Wound Healing: Effects of a Multicomponent, Multitarget Natural Product Therapy-Tr14 - St. Laurent, Georges; Seilheimer, Bernd; Tackett, Michael; Zhou, Jianhua; Shtokalo, Dmitry; Vyatkin, Yuri; Ri, Maxim; Toma, Ian; Jones, Dan; McCaffrey, Timothy A. (Frontiers in Molecular Biosciences, 2017)
Wound healing involves an orchestrated response that engages multiple processes such as hemostasis, cellular migration, extracellular matrix synthesis, and in particular, inflammation. Using a murine model of cutaneous wound repair, the transcriptome was mapped from 12 hours to 8 days post-injury, and in response to a multicomponent, multi-target natural product, Tr14. Using single-molecule RNA sequencing (RNAseq), there were clear temporal changes in known transcripts related to wound healing pathways, and additional novel transcripts of both coding and non-coding genes. Tr14 treatment modulated >100 transcripts related to key wound repair pathways such as cellular differentiation, wound contraction, and cell mobility. The results provide the most precise and comprehensive characterization to date of the transcriptome’s response to skin damage, repair, and multicomponent natural product therapy. By understanding the wound repair process, and the effects of natural products, it should be possible to intervene more effectively in diseases involving aberrant repair.